2008
DOI: 10.1203/pdr.0b013e31817d9c35
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Breathing Patterns of Very Preterm Infants Treated With Continuous Positive Airway Pressure at Birth

Abstract: There are no data describing how very preterm infants breathe spontaneously immediately after birth. We studied a convenience sample of spontaneously breathing infants Յ32 wk' gestation treated with facemask continuous positive airway pressure at birth. Airway pressure and flow were measured and each breath analyzed. Twelve infants had 792 breaths suitable for analysis. Results are given as mean (SD). Gestational age and birth weight were 29 (1.9) wk and 1220 (412) g. Recordings were started 159 (77) s after b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 53 publications
2
45
0
Order By: Relevance
“…more air is inspired than exhaled [45]. ‘Air-trapping' could occur due to braking of expiration, which was described previously as ‘frog breathing' [46,47,48]. Karlberg and Koch [47], using chest X-rays and reverse plethysmography, described the first breath as a deeper and slower breath than subsequent breaths, composed of a large inspiration followed by a braked, slow expiration.…”
Section: Pulmonary Transitionmentioning
confidence: 99%
“…more air is inspired than exhaled [45]. ‘Air-trapping' could occur due to braking of expiration, which was described previously as ‘frog breathing' [46,47,48]. Karlberg and Koch [47], using chest X-rays and reverse plethysmography, described the first breath as a deeper and slower breath than subsequent breaths, composed of a large inspiration followed by a braked, slow expiration.…”
Section: Pulmonary Transitionmentioning
confidence: 99%
“…Term and preterm infants begin to breathe after delivery with deep inspirations and braking of expirations (3)(4)(5)(6)(7). Closure of the larynx during expiration may help the newborn to maintain FRC (6,8).…”
mentioning
confidence: 99%
“…In human neonates, V T s of 6.4 (4.1) ml/kg have been observed in term infants and Establishing lung gas volumes at birth Articles 6.7 (3.9) ml/kg in preterm infants, although it is unlikely that the very first breaths after birth were recorded in this study (29). In a separate study of babies receiving continuous positive airway pressure at birth, a variety of different respiratory patterns were observed with V T ranging from mean (SD) 3.1 (1.7) to 7.5 (4.2) ml/kg (30). Although evidence is lacking in preterm human infants, spontaneously breathing newborn rabbits appear to use large V T s (≈15 ml/kg) at the onset of air breathing, which gradually decrease with increasing breath number.…”
Section: Tmentioning
confidence: 69%
“…Although an arbitrary range of 4-8 ml/kg is considered to be the optimal V T range to target when ventilating preterm human infants, a recent study has demonstrated that many of the volumes delivered during resuscitation are inadvertently well outside this range (33). It is clear that some spontaneous breathing infants initiate tidal breathing exceeding 8 ml/kg (29,30). In newborn rabbits, V T reduces as aeration occurs (19).…”
Section: Tmentioning
confidence: 99%